Identifikasi Bakteri Gram Negatif Galur Extended Spectrum Beta Lactamase Pada Ruang NICU RSUD Prof. DR. W. Z. Johannes Kupang - Norma Tiku Kambuno; Dicky Fanggidae (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Extended Spectrum Beta-Lactamase (ESBL) is an enzyme that is capable of hydrolyzing antibiotics from penicillin groups, the generation I, II, III cephalosporins, and monobactam. ESBL is most commonly isolated from Enterobacteriaceae, especially Escherichia coli and Klebsiella pneumonia. The spread of ESBL-producing Enterobacteriaceae can also occur due to mutations. Cases of ESBL detection in hospitals have been widely reported throughout the world including Indonesia. The purpose of this study was to identify Enterobacteriaceae which included ESBL strains isolated from the NICU room of RSUD Prof. Dr. W. Z. Johannes Kupang in 2015. This study was a descriptive study with a cross-sectional approach. The samples used were 18 swab specimens from room facilities collected by accidental sampling method. Swab specimens are grown in Blood Agar Plate and Mac Conkey Agar. Bacterial identification methods are equipped with microscopic tests and biochemical tests. Klebsiella sp was identified and then followed by the antimicrobial sensitivity test (Kirby Bauer) against ceftazidime and ceftriaxone. ESBL confirmation test uses the Double Disc Sinergy Test (DDST) method. The results of the antibiotic sensitivity test showed Klebsiella sp. resistant to the antibiotics ceftazidime and ceftriaxone. DDST test shows ESBL production from Klebsiella sp. It was concluded that ESBL-producing Enterobacteriaceae found were Klebsiella sp which had shown resistance to third-generation cephalosporins (Ceftazidime and Ceftriaxone).